A influência do ruído ambiental nos movimentos sacádicos, na atenção concentrada e na leitura de crianças de 9 e 10 anos - Carmo, Michele Picanço do (2016)
Introduction: Noise can adversely affect cognitive performance, influencing in cognition, short-term memory, attention, executive functions, reading and writing, impairing cognitive performance and learning in children school age. Brazilian schools have noise levels above the recommended for acoustic comfort, which can interfere with the learning process. Objective: To investigate the effect of environmental noise in saccades, in concentrated and reading in a group of children with reading and writing alterations attention. Methods: We evaluated 42 children aged 9 to 10 years no hearing impairment, visual or reading and writing. Saccades were evaluated by Electronystagmography; attention was measured by Attention Test for Cancellation and the reading was assessed using Prova Brasil text. The tests were performed in the situation of silence and background noise of 76 dB (A) and 95 dB (A), previously measured in the classroom. Results: Noise caused no significant effect on speed, accuracy and latency of saccadic movements as well as the number of errors, successes, omissions and absences in attention test. In reading test were found differences in speed in the presence of noise. When exposed to 76 dB (A) and 95 dB (A) children read fewer words per minute than in silence. Conclusion: No significant noise effect in the tests, may be due to early exposure to noise, causing a habituation to noise. One can also think that the type of distractor used, cafeteria noise, was not enough to bring about the expected effects